PROBLEMS AND CHALLENGES FACED BY THE ASSAMESE LANGUAGE IN THE 21ST CENTURY - Dimpi Das (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In the 21st century, the minds and thought processes of people all over the world are changing rapidly due to the powerful wave of globalization. This is also affecting the linguistic structure of many communities worldwide. Science and technology is making everything easy for people but threatening the existence of the Assamese language. In the 21st century, the Assamese language is facing many problems. Some of them are- negligence towards one’s mother tongue, the ignorance of the middle class Assamese, the adverse effects of electronic media, immigration, globalization etc.